Perceptions of art and design faculty on the instructional value of iPads - Souleles, Nicos; Savva, Stefania; Watters, Hilary; Annesley, Angela (My University, 2017)
The widespread use of iPads in higher education brings to the forefront questions about the contribution of these computer tablets towards teaching and learning. However, there is a noticeable gap in research on the educational potential of iPads in higher education. This article describes the second stage of a research project on the use of iPads in undergraduate art and design disciplines, and in particular the views and experiences of faculty in two different art and design schools over a period of one semester. The first stage of the project investigated the perceptions of art and design students about the educational value of iPads. For the second stage, the unified theory of acceptance and use of technology model was used to gauge adoption of the iPad for teaching and learning, and the participants provided qualitative data that was used for this phenomenographic study. The outcomes of this investigation provide an overview of challenges and obstacles from the perspective of art and design faculty in embedding the use of iPads in teaching and learning.
Keywords: Art and design; Faculty; Perceptions; Phenomenography; Technology acceptance models; iPad